Fruit and vegetable supply to schools - Preston, Nicola (Cranfield University, 2001)
This report, sponsored by the Fresh Produce Consortium (FPC), describes the supply chain for fresh fruits and vegetables consumed as part of school meals. FPC had previously identified schools serving children in the 4-11 years age group as being the segment of specific interest. The report also presents an insight into the decision making processes and purchasing arrangements at the different points in the supply chain. The study involved identifying the factors that will determine the level of demand for fresh produce within the school meals sector. In addition, FPC wanted to assess the likely impact of the government's move towards transferring responsibility for the management of school budgets from Local Education Authorities (LEAs) to the schools themselves on demand for fresh produce in schools. Within the education sector, this initiative is referred to as Fair Funding. The methods employed in this research were eclectic in nature. In order to describe decision making within the supply chain a series of personal and telephone interviews were conducted within the context of a multiple case study design. The interview data were analysed using content analysis. In addition, several databases were constructed that will allow FPC to conduct targeted marketing programmes. The databases are: (1) UK schools serving 4-11 year old children, (2) LEA caterers, (3) Contract caterers. The principal conclusions reached are that demand for fresh produce, within the schools meals sector, is likely to grow noticeably over the next 5 years. This growth will be driven by the government's decision to invest in 'free fruits in schools' and initiatives taken to change children's behaviour with respect to the consumption of fresh fruits and vegetables. Moreover there is a concerted effort on the part of government, health professionals, the food industry and pressure groups towards improving the diet of the nation and this too will impact on fresh produce demand in the school meals sector.